A final report on practice in industry - Conlu, Ambrosio F.
The college of fisheries, university of the Philippines has been molding the students for the last two and one half years in order to attain the prime objective of the school, to train responsible men and women i9n their chosen vocation, fishing. However the two and half years theoretical and practical instruction given to the students are not enough to meet the more practical aspects of the vocation. Thus a six-month practice in industry is required by the school to every student who has accomplished all the requirements in his or her academic subjects. The practice in industry is a prerequisite to graduation, whereby the student undergoing such training is expected to have a varied experience in fishing. That is, every month students taking the fish capture course must practice the use of different kinds of gear so that the student could have a better idea of gears that we had actually observed in the field. During the period of apprenticeship, the students in the field can apply the different theories and practices learned from the classroom and at the same time learn the techniques of the experienced fisherman. Not only learning and applying the different techniques, but also developing public relations and studying the socio-economic standard of the fisherman who he may contact during his training. The students are out on practical training with such a complicated objective, but the most important is the know-how of fishing methods to be learned from the experienced fisherman.